Orçamento participativo e a formação para a cidadania - Araujo, Margarete Panerai (1999)
Our research intends to investigate the process of education for the practice of citizenship made possible since 1989, thorough the Pariticipatory. Budget m the cíty of Porto Alegre. That strategícal system of administratíon of public resources became an example of the people's participation in the social area it has become even an instrument-symbol of the city, because its techniques contribute to draw a new profile of the education for the practice of citizenship. Our methodology, according to our objective of investigating the nature of the education tor the practice of citizenship offered by the Particípatory Budget has used as techniques of procedures documentary and biblíographical research, besides direct contact with several agents. Toe research ínstruments employed in the collections of data, analysis and interpretation, carried on the following techniques: interviews with the regional counselors of the people and with the representatives of thematic committees (elected representatives in the process of the Participatory Budget); documentary collection, analysis carried out were: Toe Participatory budget, the education for the practice of the citizenship and the political, ideological conduct (as a knowledge acquired, a credit property), and/or capital which indicate an incorporated disposition, almost a mie made by the municipality). This research 1s unprecedented' never before experieneed) due to the utilization of the theoretical- methodological project of french sociologist Pierre Bourdieu. Its results have shown that so as to assure, on a municiplality levei, the transfer of the power of decision of the public investments to the citizens of Porto Alegre offers a process of politicization that becomes more and more ample through the participation, autonomy and consequential formation of new conduct, heading towards an administration complying with proper norms. Considering that the process of formation favoured by the participatory budget assures a personal appreciation of the social agents, thus making possible the progress of the citizen. The education for the practice of citizenship consequently, offered by those prectices durino ten years consecutively, is achievig intemational recognition that excels itself in the political scenario of the twentieth century.